Effect of ultrasound waves, chilling and mechanical abrasion on dormancy-breaking and germination characteristics of Datura stramonium and Convolvulus arvensis - Hajar Ghafoori; Eshagh Keshtkar; Majid Aghaalikhani; Alireza Mahdavian (علوم و فناوری بذر ایران)
The phenomenon of seed dormancy in weeds not only lead to management difficulties over time but also can disrupt the biological, morphological and ecological studies carried out on these species. This study was conducted to investigate the effect of ultrasound on seed dormancy breaking of Datura stramonium and Convolvulus arvensis in laboratory conditions. Two separate experiments were conducted as a completely randomized design with four replications for each species. The ultrasonic waves were applied at five powers including 0, 80, 150, 250 and 350 watts for four and eight minutes, where the applied ultrasonic frequency was 20 kHz and the temperature of water was remained constant at 25°C. In addition to the ultrasound treatments, the common dormancy-breaking treatments including chilling (natural chilling, moist chilling and dry chilling) and mechanical scarification were applied on D. stramonium and C. arvensis, respectively. All sonication treatments decreased accumulated maximum germination (Gmax) of both weed species. Also, the ultrasound treatments increased time to 50% of maximum germination (G50) of D. stramonium. The ultrasonic effect on G50 of C. arvensis was depended on ultrasonic power, where at low ultrasound powers the G50 of D. stramonium was similar to untreated seeds, while it was decreased at high ultrasound powers. Accordingly, ultrasound was not a suitable method to break seed dormancy of D. stramonium and C. arvensis. As the best treatments, the natural chilling and mechanical scarification increased Gmax of D. stramonium and C. arvensis up to 49% and 38%, respectively.